Trabalho docente, campo e habitus em colégios da Polícia Militar do estado de Goiás - Linhares, Sebastião Donizeti da Silva (2022)
This dissertation was developed within the scope of the Postgraduate Program in Sociology of the Faculty of Social Sciences of the Federal University of Goiás (PPGS/UFG), in the line of research “Work, formation and Cultural Representations”. Its main objective is to analyze the teaching work in military policy colleges in the State of Goiás and the specific objectives are to apprehend the subjectivity of the agents who are inserted in this form of field and their representation in the military police colleges.; to identify the conditions for the formation of a field and a military habitus within the school units called CPMG –Colégio da Polícia Militar de Goiás; to characterize the conditions and forms of organization and contracting of work in the CPMG; to analyze the professional and behavioral change for workers who start to experience a form of military education having work in civil education; understand how work happens within a field, that of military education in the State of Goiás and the construction of a corresponding habitus. The methodology used involved bibliographic research, quantitative analysis of governmental databases (INEP) and of an elaborated survey and qualitative analysis of semi-structured interviews with teachers from the selected schools). The process of militarization of part of the schools in the State of Goiás began in the middle of the years 1999 to 2000, thus generating a specific school field from a typically military management. This study leaves as a benefit a bibliographic survey on field theory and habitus in Pierre Bourdieu, as well as a survey and compilation of updated data on schools of military management; relevant aspects about the way of working and subjectivity of agents (teachers) within this field of work.